Surface Vaporization of High-Strength Aluminum Alloy During Electron-Beam Welding; Russian Physics Journal; Vol. 65, iss. 3 - Solovev V. V. Vasilii Vasilevich; Damer V. Vladislav; Bleykher (Bleicher) G. A. Galina Alekseevna; Krivobokov V. P. Valery Pavlovich (2022, 2022)
Title screen